Urban Prophets: Creating Graffiti as a Means of Negotiating the Constructs of Urban Public Spaces - Fraser, Alison (Stream: Interdisciplinary Journal of Communication, 2016)
For this examination, graffiti and neo-graffiti have been compared to public art in order to reveal the ideological constructions of urban public spaces. How does graffiti interact with the construction of urban public spaces? How is graffiti similar to and different from public art? Which of these art forms better represents the public and city living? By comparing public art to (neo)graffiti in Toronto, Ontario and Los Angeles, California, the gendered, racialized, and class-based exclusions present in R. Florida's (2002) creative cities framework as theorized by authors such as N. Smith (1996), Sharon Zukin (1996), and G. Standing (2011) can be revealed. Urban public spaces are carefully shaped by those in control, the government and corporations, with the intention of creating spaces and citizens within those spaces that can be a functioning part of their neoliberal capitalist system. Graffiti and neo-graffiti act as a visual interruption to this system, which in turn can be thought of as physically represented by public art. In this way (neo)graffiti is created by a minority of citizens with the hopes of reclaiming their right to exist in urban public spaces despite layers of ideological exclusions.For this examination, graffiti and neo-graffiti have been compared to public art in order to reveal the ideological constructions of urban public spaces. How does graffiti interact with the construction of urban public spaces? How is graffiti similar to and different from public art? Which of these art forms better represents the public and city living? By comparing public art (neo)graffiti in Toronto, Ontario and Los Angeles California, the racialized and class-based exclusions present in R. Florida’s (2002) creative cities framework theorized by authors such as N. Smith (1996), Sharon Zukin (1996), and G. Standing (2011) can be revealed. Urban public spaces are carefully shaped by those in control (the government and corporations) with the intention of creating spaces and citizens within those spaces that can be a functioning part of their system. Graffiti and neo-graffiti act as a visual interruption to this system as represented by public art. In this way (neo)graffiti is created by a minority of citizens with the hopes of reclaiming their right to exist in urban public spaces despite the layers of exclusions.